Hair cell BK channels interact with RACK1, and PKC increases its expression on the cell surface by indirect phosphorylation - Surguchev, Alexei (American Physiological Society, 2012)
Large conductance (BK) calcium activated potassium channels (Slo) are ubiquitous and implicated in a number of human diseases including hypertension and epilepsy. BK channels consist of a pore forming α-subunit (Slo) and a number of accessory subunits. In hair cells of nonmammalian vertebrates these channels play a critical role in electrical resonance, a mechanism of frequency selectivity. Hair cell BK channel clusters on the surface and currents increase along the tonotopic axis and contribute significantly to the responsiveness of these hair cells to sounds of high frequency. In contrast, messenger RNA levels encoding the Slo gene show an opposite decrease in high frequency hair cells. To understand the molecular events underlying this paradox, we used a yeast two-hybrid screen to isolate binding partners of Slo. We identified Rack1 as a Slo binding partner and demonstrate that PKC activation increases Slo surface expression. We also establish that increased Slo recycling of endocytosed Slo is at least partially responsible for the increased surface expression of Slo. Moreover, analysis of several PKC phosphorylation site mutants confirms that the effects of PKC on Slo surface expression are likely indirect. Finally, we show that Slo clusters on the surface of hair cells are also increased by increased PKC activity and may contribute to the increasing amounts of channel clusters on the surface of high-frequency hair cells.